PEMBAHARUAN SISTEM PERADILAN DI INDONESIA PADA LEMBAGA KEJAKSAAN DALAM FUNGSI PENYIDIKAN - Restu Monika Nia Betaubun; Cavin George Ngilawane (Jurnal Restorative Justice, 2022)
The central position of the Indonesian Prosecutor's Office in law enforcement in Indonesia, as one of the legal sub-systems that are in an organized and integrated unit, influences and complements each other with other sub-systems to achieve the objectives of the legal system. Judging from the aspect of its authority, the prosecutor has the authority to carry out investigations and prosecutions, but the first part in the function of carrying out investigations, the prosecutor's authority is limited to certain crimes, such as criminal acts of sedition, economic crimes and criminal acts of corruption. In this short paper, the author tries to give a little contribution to the idea of ​​reforming the justice system in Indonesia, especially at the prosecutor's office in the investigative function. The formulation of the problem includes how the system of reforming the prosecutor's office in carrying out the investigation function. The type of legal research used is the type of normative legal research which focuses on the laws and regulations regarding Law Number 16 of 2004 concerning the Attorney General's Office of the Republic of Indonesia, the approach used is the legal history approach. This approach is to find out the history of the prosecutor's duties as investigators. The results of this study are that in their duties as conducting investigations the prosecutor can conduct investigations if the crimes are complex or the level of proof is difficult, for example crimes in the field of human rights and corruption, and if the prosecutor is given additional authority such as participating in further investigations to act as a prosecutor. In general, if the case is transferred to the court, the author feels that the prosecutor can be responsible for the prosecution of a case in its entirety because from the beginning it was directly involved from the investigation process to the prosecution, and in the investigation process if the prosecutor participates it will eliminate the situation of back and forth between the investigator and the file. public prosecutor.